Flap endonuclease 1 (FEN1) biomarker as a new diagnostic target for the biosensing of cancer - Saba Mahboubi; Mehdi Evazalipour; Ehsan Zamani; Nozhat Zebardast; Alireza Farokhrouz; Rahim Nosrati (Sensors and Actuators Reports)
Flap endonuclease 1 (FEN1) is a structure-specific nuclease that plays a role in DNA replication and genome stability. FEN1 is overexpressed in proliferative cancers and correlates with the grade and aggressiveness of the cancer, suggesting that it could potentially be considered a promising biomarker for various cancer types. Due to the initiation of cancer is related to the lack of the activity of FEN1 nuclease, the detection and quantification of FEN1 is significance for cancer diagnosis in early stage. There are various approaches to detect the different types of cancer biomarkers. In this context, biosensing platforms and nanotechnology-based methods have attracted much attention. To date, the sensitivity and performance of biosensors can enhance by nanomaterials/nanoparticles that have been incorporated in biosensing platforms. This review overview a brief classification and description of the advancement of biosensors and nanobiosensors for the detection and quantitation of FEN1 based on optical and electrochemical platforms.